Multiple Supernumerary Teeth in a Non-Syndromic Patient: A Case Report - Majid Eshgh Pour; Reza Shahakbari; Baratollah Shaban (Mashhad University of Medical Sciences, 2013)
Introduction: Multiple supernumerary teeth are a rare phenomenon. It occurs more often in patients with syndromes such as Gardner's syndrome, cleidocranial dysplasia and so on. This phenomenon in absence of such syndromes is rare. The purpose of this report was to introduce a case of non-syndromic multiple supernumerary impacted teeth.Case Report: A 29-year-old woman with no skeletal, metabolic, systemic and mental disorder was referred to oral and maxillofacial department of Mashhad dental school. In clinical evaluation, seven Permanent teeth were missing. In radiographic evaluation, there were a total of 15 impacted teeth which 7 of them were supernumerary.Conclusion: Missing or Excess of one or more teeth usually leads to occlusal and functional problems. In these cases, a complete clinical and radiographic examination accompanieal by a precise history should be performed to plan a suitable surgical-orthodontic-prosthetic treatment.